2019
DOI: 10.1080/10428194.2019.1623886
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in treatment and survival of older adult diffuse large B-Cell lymphoma patients in the SEER-Medicare linked database

Abstract: To describe temporal trends in treatment among older adult (!66 years) patients diagnosed with diffuse large B-cell lymphoma (DLBCL), we analyzed 18,058 DLBCL patients from the Surveillance, Epidemiology, and End Results linked Medicare (SEER-Medicare) database diagnosed between 2001 and 2013. Among 65% of patients receiving treatment after diagnosis, R-CHOP (Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, Prednisone) was the most common frontline therapy, increasing with more recent treatment year: 51%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
3
10
1
Order By: Relevance
“…Stratified Kaplan-Meier survival analyses showed worse survival with increasing age, male gender, and use of chemotherapy without R. Such trends were also observed in an US SEER registry study [23]. Association of R-based regimens with higher survival rates has been suggested in earlier reports [4,8,9].…”
Section: Plos Onesupporting
confidence: 69%
See 1 more Smart Citation
“…Stratified Kaplan-Meier survival analyses showed worse survival with increasing age, male gender, and use of chemotherapy without R. Such trends were also observed in an US SEER registry study [23]. Association of R-based regimens with higher survival rates has been suggested in earlier reports [4,8,9].…”
Section: Plos Onesupporting
confidence: 69%
“…This analysis classified patient's 1L regimen based on their first treatment during the identification period and required at least 6 months of look-back with a DLBCL diagnosis. Most patients were assumed to be treatment naïve, and based on the 1L regimen distribution, the results were consistent with prior literature [23]. Another limitation was that mortality data were captured only through patient's hospital discharge records, making OS results less robust.…”
Section: Plos Onesupporting
confidence: 55%
“…For both autologous HCT and stem cell collection, only incident outcomes were considered. We obtained CPT and ICD codes through a focused literature review, American Society of Transplantation and Cellular Therapy billing guidelines, discussion with billing physicians, and manual review of codes 11 . We used a combination of inpatient and outpatient billing codes to avoid missing outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained CPT and ICD codes through a focused literature review, American Society of Transplantation and Cellular Therapy billing guidelines, discussion with billing physicians, and manual review of codes. 11 We used a combination of inpatient and outpatient billing codes to avoid missing outcomes. We identified outcomes at any point following the diagnosis of lymphoma.…”
Section: Methodsmentioning
confidence: 99%
“…80 years v 71% in patients up to 80 years). 10 Outcomes have been found to be inferior in patients who do not complete R-CHOP therapy. 11 In a retrospective, single-center study of 115 previously untreated patients, Kwak et al 12 identified an actual relative dose intensity of doxorubicin .…”
Section: Introductionmentioning
confidence: 99%